Analisis Literasi Keuangan, Efikasi Diri, dan Persepsi Risiko terhadap Minat Investasi Dimoderasi Kemajuan Teknologi Investasi - Abdillah, Moh. Ansyar; Hariyati, Hariyati; Hakim, Luqman (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
The purpose of this study was to understand the influence of financial literacy, self-efficacy, and risk perception on investment interest, as moderated by advances in investment technology. The study utilized 105 university students in Surabaya as respondents. The analysis results provided evidence of a significant partial influence of financial literacy, self-efficacy, and risk perception on students' investment interest. Another finding was that advances in investment technology were proven to moderate the influence of financial literacy, self-efficacy, and risk perception on students' investment interest. Based on the results, it is recommended that students further improve their financial literacy, build self-efficacy by starting to invest gradually, and understand risk rationally. With the synergy between education, psychological factors, and technology, students' investment interest is expected to increase optimally.